Breast Cancer Detectability and Tumor Differentiation based on Microwave Dielectric Property Changes with Reverse Time Migration - Aydinalp, Cemanur; Yıldız Altıntaş, Gülşah (Balkan Journal of Electrical & Computer Engineering (BAJECE), 2025)
Breast cancer detection and treatment have advanced significantly with imaging technologies, but challenges remain in distinguishing the type and stage of tumors. Microwave imaging (MWI) offers a promising alternative due to its non-ionizing nature and its ability to exploit dielectric property (DP) contrast. This study investigates the effectiveness of MWI in detecting and characterizing tumors using a phantom for breast tissue and tumor-mimicking NaCl solutions with various DPs (0.1 M, 0.2 M, 0.4 M and 0.8 M). First, the Cole-Cole parameters of these materials were calculated using DP measurements obtained from the open-ended coaxial probe method in order to provide broadband frequency analysis. Furthermore, the developed MWI system was utilized to evaluate tumor detectability and differentiation based on these DP changes. The MWI experiment was performed with 12 Vivaldi antennas between 0.6-2.6 GHz and the results were analyzed for two different positions. The results indicate that MWI system can effectively distinguish tumors with different DPs from each other using quantitative differential imaging due to its sensitivity to variations. To this end, the inverse time migration (RTM) method was employed to compare reference-target pairs (RTP) to generate an image of a tissue-mimicking phantom with tumors. The results show high correlation between RTP image contrast and the target-reference DP difference.